2017
DOI: 10.1093/cercor/bhx250
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Cortical Neuron DNA Methylation Profile in Autism Spectrum Disorder

Abstract: Autism Spectrum Disorder (ASD) is a complex neuropsychiatric syndrome whose etiology includes genetic and environmental components. Since epigenetic marks are sensitive to environmental insult, they may be involved in the development of ASD. Initial brain studies have suggested a dysregulation of epigenetic marks in ASD. However, due to cellular heterogeneity in the brain, these studies have not determined if there is a true change in the neuronal epigenetic signature. Here, we report a genome-wide methylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(92 citation statements)
references
References 70 publications
7
82
2
1
Order By: Relevance
“…Gene lists were sourced from the reported hits of each paper [6,12,[21][22][23][24][25][26][27][28][29][30][37][38][39][40][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103].…”
Section: Autism Gene Enrichmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene lists were sourced from the reported hits of each paper [6,12,[21][22][23][24][25][26][27][28][29][30][37][38][39][40][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103].…”
Section: Autism Gene Enrichmentmentioning
confidence: 99%
“…Epigenome-wide association studies (EWAS) have identified locus-specific differential methylation and epigenetic signatures associated with ASD. EWAS in post-mortem brain have identified differential methylation of genes involved in synaptic transmission and the immune response, with a particular enrichment for open chromatin regions and genes important for microglia [21][22][23][24]. Similarities in brain epigenetic dysregulation have been found between individuals with idiopathic and syndromic ASDs, including Dup15q and Rett syndrome [23,25,26].…”
mentioning
confidence: 99%
“…Both genetic and environmental factors are believed to be involved in the etiology of ASD and other neurodevelopmental disorders. DNA methylation has been proposed as an epigenetic interface which links environmental factors to genomic susceptibility in ASD [64,65] and neurodevelopment [66]. MBD proteins as readers of DNA methylation are therefore potential mediators which translate the altered DNA methylation landscape into gene-expression and ultimately behavioral changes.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we examined the enrichment of nonpsychiatric disorder‐associated genes in each module. The lists of genes associated with atherosclerosis, diabetes mellitus (DM) type 2, and systemic lupus erythematosus (SLE) were obtained from Nardone, Sams, Zito, Reuveni, and Elliott (). We performed a mouse phenotype enrichment analysis using the following mouse phenotype (MP) ontology terms from the Mouse Genome Informatics (MGI) database (Eppig, Blake, Bult, Kadin, & Richardson, ): abnormal social behavior [MP:0002557], abnormal fear/anxiety behavior [MP:0002065], and abnormal learning/memory [MP:0002063].…”
Section: Methodsmentioning
confidence: 99%